A Smart Polymeric Sol‐Binder for Building Healthy Active‐Material Microenvironment in High‐Energy‐Density Electrodes. Issue 6 (23rd December 2022) - He, Yan; Jing, Lei; Feng, Lanxiang; Yang, Sifan; Yang, Jiarui; Fu, Xuewei; Yang, Wei; Wang, Yu
Abstract: Similar to the cell microenvironment in biology, the active material microenvironment (ME@AM) in battery electrodes determines the charge flux into/out the individual AM particles, and the overall device performance thereby. However, it is very challenging to understand and regulate the ME@AM structures due to the lack of advanced binders and their links to electrode microstructures. Here, to address this challenge, a high‐performance sol‐binder based on propylene carbonate (PC) and poly(vinylidene fluoride) is designed and the ME@AM structural evolution during its electrode fabrication is investigated. First, a pen‐ink‐like uniform slurry is successfully prepared in minutes with the PC solvent. Second, the sol‐to‐gel transition of the sol‐binder during high‐temperature drying suppresses the uncontrollable component aggregation/separation as generally found in conventional solution‐based slurries. Third, it helps to build robust and healthy ME@AM with a high mechanical state‐of‐health (97%) and 800% improvement in peeling strength, because of an optimized enriched binder distribution. Finally, thick lean‐binder electrodes are demonstrated with much improved overall electrochemical performance. This study not only uncovers the potential of polymer sols or colloids as advanced binders, but also reshapes the understanding of electrode microstructures and their links to binder systems through the concept of ME@AM. Abstract : A high‐performance polymeric sol‐binder is proposed to build a "healthy" active material microenvironment (ME@AM), which may reshape the understanding of electrode microstructures as well as the roles of binder systems.